Future trends in international migration - Heiko Körner (Intereconomics, 1991)
According to a projection by the World Bank, international migration will decline significantly over the next decade. This projection not only assumes a narrowing of the welfare gap between industrialised and developing countries. It also sets out from the premise that potential migrants react to changes in the economic and social conditions in their home countries with more or less constant (negative) migration elasticities. The following article shows that there is reason to question the validity of this assumption.
Keywords: 330